Optimal Determination of Size and Site of DGs in Mesh System Using PSO - Mohammad Salehi Male; Adel Akbari Majd; Ramtin Rasouli Nezhad (Institute of Advanced Engineering and Science, 2014)
Nowadays, the penetration of Distributed Generation (DG) in power networks takes special place for them worldwide and is increasing in developed countries. In order to improve of voltage profile, stability, reduction of power losses and etc, it is necessary that this increasing of installation of DGs in Distribution system should be becomes systematically. This paper introduces an optimal placement method in order to sizing and sitting of distributed generation in IEEE 30 bus mesh test system. The algorithm for optimization is Particle Swarm Optimization (PSO). Proposed objective function is Multi Objective Function that considers active power losses of the system and the voltage profile. High performance of the proposed algorithm is proved by applying algorithm in 30 bus IEEE system using MATLAB software and in order to illustrate of feasibility of proposed method this optimization will achieved with Three DG units.